Functional Metaplasticity of Hippocampal Schaffer Collateral-CA1 Synapses Is Reversed in Chronically Epileptic Rats - Mirko Rehberg; Timo Kirschstein; Xiati Guli; Steffen Müller; Marco Rohde; Denise Franz; Tursonjan Tokay; Rüdiger Köhling (Neural Plasticity)
Spatial learning and associating spatial information with individual experience are crucial for rodents and higher mammals. Hence, studying the cellular and molecular cascades involved in the key mechanism of information storage in the brain, synaptic plasticity, has led to enormous knowledge in this field. A major open question applies to the interdependence between synaptic plasticity and its behavioral correlates. In this context, it has become clear that behavioral aspects may impact subsequent synaptic plasticity, a phenomenon termed behavioral metaplasticity. Here, we trained control and pilocarpine-treated chronically epileptic rats of two different age groups (adolescent and adult) in a spatial memory task and subsequently tested long-term potentiation (LTP) in vitro at Schaffer collateral—CA1 synapses. As expected, memory acquisition in the behavioral task was significantly impaired both in pilocarpine-treated animals and in adult controls. Accordingly, these groups, without being tested in the behavioral training task, showed reduced CA1-LTP levels compared to untrained young controls. Spatial memory training significantly reduced subsequent CA1-LTP in vitro in the adolescent control group yet enhanced CA1-LTP in the adult pilocarpine-treated group. Such training in the adolescent pilocarpine-treated and adult control groups resulted in intermediate changes. Our study demonstrates age-dependent functional metaplasticity following a spatial memory training task and its reversal under pathological conditions.